Determination of anticancer effects of Urospermum picroides against human cancer cell lines - Mehlika Alper; Hatice Güneş (International Journal of Secondary Metabolite)
Plants continue to be a good source for developing effective anticancer agents. In this study, in vitro various biological effects of crude ethanolic extract from flowering parts of Urospermum picroides collected from the Muğla province of Turkey were investigated for the first time. Daudi, A549 and HeLa cancer cell lines and BEAS-2B normal cell line were used to identify the cytotoxic effect of the extract using MTT assay. The effect of the extract on cell cycle progression was detected by flow cytometric analysis. The level of VEGF, IL-1α, IL-6 and TNF-α secretion in the cells treated with the extract were measured using ELISA The extract caused a higher cytotoxic effect on Daudi cells with an IC50 value of 85.64 µg/mL than the other cells tested. The IC50 values in HeLa and A549 cells were determined to be 135.35 and 234.8 µg/ mL, respectively. The selective cytotoxicity was considered between Daudi and BEAS-2B (109.80 µg/mL) cell lines. In addition, the effect of the extract on cell cycle progression changes according to cell line used. Moreover, the extract decreased the level of secreted VEGF in treated A549 cells by 31%. In addition, the extract resulted in a significant decrease in the secretion of IL-1α, IL-6 and TNF-α cytokines in A549 and Daudi cells compared to the untreated cells. These findings suggest that the flowering parts of U. picroides may be a potential source for anticancer agents.